2015
DOI: 10.1177/1352458515575338
|View full text |Cite
|
Sign up to set email alerts
|

Should we systematically test patients with clinically isolated syndrome for auto-antibodies?

Abstract: Antinuclear-antibodies, anti-SSA and anti-SSB should not be routinely determined in CIS patients but only in those presenting symptoms suggestive of other ADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Are they real false‐positive results or, as for autoantibodies sometimes present in MS patients (antinuclear antibodies, anti‐SSA, or anti‐SSB), are they a concurrent association without a necessarily clinical significance? [14]. The scarcity of MOG‐IgG among healthy individuals (less than 0.1%) appears to support the second hypothesis [15].…”
Section: Discussionmentioning
confidence: 86%
“…Are they real false‐positive results or, as for autoantibodies sometimes present in MS patients (antinuclear antibodies, anti‐SSA, or anti‐SSB), are they a concurrent association without a necessarily clinical significance? [14]. The scarcity of MOG‐IgG among healthy individuals (less than 0.1%) appears to support the second hypothesis [15].…”
Section: Discussionmentioning
confidence: 86%
“…In a long-term follow-up study conducted with clinically isolated syndrome type MS patients, there was no significant correlation between ANA positivity and clinical, laboratory and radiological parameters, and also no significant difference between MS patients and the general population in the rate of patients with antibody positivity who developed autoimmune diseases. Thus, they concluded that autoantibody studies are not useful in the absence of clinical findings [11]. In another ACE -angiotensin-converting enzyme; aCL -anticardiolipin; AMA -anti-mitochondrial antibodies; ANA -anti-nuclear antibody; ANCA -antineutrophil cytoplasmic antibodies; Anti-SSB -anti-Sjögren's-syndrome-related antigen B; Anti-TPO -anti-thyroid peroxidase antibodies; Auto-Ab -autoantibody; DFS-70 -anti-dense fine speckled-70 antibodies; ENA -extractable nuclear antigen; LA -lupus anticoagulant; MS -multiple sclerosis steroid treatment, family history, presence of comorbidity, presence of autoimmune disease, or EDSS scores recorded at the end of the two-year follow-up period (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The rate of MS patients with ANA positivity reported in the literature ranges between 3.6% and 63.5% [7]. Although the clinical significance of the prevalence of ANA positivity in MS patients situation is not yet clear, some studies have stated that ANA positivity is associated with disease activity, while others have reported that ANA positivity will not have a clinical significance unless there are systemic symptoms indicating an underlying connective tissue disorder [11,12]. Different studies have reported the prevalence of anticardiolipin antibody (aCL) in MS patients of between 4.8% and 44%, and did not find any significant difference between MS patients and healthy controls in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the standard diagnostic process for multiple sclerosis, blood tests are frequently required. Routine autoantibody testing, however, is not always helpful for individuals who have a typical CIS [26]. As a result, it would be sensible to test for autoantibodies only in the presence of other symptoms that are indicative of other autoimmune illnesses.…”
Section: Diagnosismentioning
confidence: 99%